Bioimpedance spectroscopy system for characterization of cancer cells - Al-hashimi, Ahmad; Nordin, Anis Nurashikin; Azman, Amelia Wong (2014)
This paper presents a design for a Bioimpedance spectroscopy system on an FPGA board for characterization of cancer cells. The proposed hardware uses a digital auto balance bridge implemented in Verilog. Using an FPGA allows the system to be designed to have a multichannel signal acquisition from two or more sources, and to be smaller than commercial devices. The simulation results show that the system is able to detect the phase and amplitude for the impedance. The design would provide a portable bioimpedance spectroscopy system, which will be able to perform calculations and show results without the need for external hardware.